DINAMIKA TENAGA KERJA SEKTOR PERTANIAN DI PROVINSI SULAWESI UTARA - L.S., Benu Olfie; Laoh, Esry O.; Montong, Sophia L.; Supartoyo, Yesi H. (Universitas Sam Ratulangi, 2010)
ABSTRACT The aim of this study was to determine the employment dynamics of agricultural sector in North Sulawesi Province. The research was conducted in Manado (July to August 2010, by using the collecting data as a secondary data research. The data was analyzed using labor share and labor force growth rate. Â The result showed that labor share of agriculture sector on the basis of education level was dominated by the level of primary education during the period 2007-2009 but its labor force growth rate had decreased each year in both rural and urban areas. On the age group was dominated by the age of 55 years and above. TheÂ employment growth rate of agriculture sector was decreased by 5.78 percent each year inÂ the period of 2000-2009. While the fenomena employment in non-agricultural sector was increased by 1.78 percent each year. This result indicated that there was tendency of structural transformation of agriculture sector to non-agricultural sector. The low tendency of trade will be able to influence farmers to reduce or to stop the agribusiness activities that will affect the size of the agiculture labor force share. Keywords: Employment Dynamics of Agricultural Sector